Three-dimensional mesostructured single crystalline Fe3O4 for ultrafast electrochemical capacitor electrode with AC line filtering performance - Kang, Jin Gu; Kim, Minjeong; Kim, Pa Do; Ju, Byeong-Kwon; Kim, Sung-Kon (John Wiley & Sons Inc., 2022)
Epitaxial growth of three-dimensional (3D) architectures has led to new opportunities in the optoelectronic devices and nanoscale thermal engineering. The feature that makes these materials distinct is to form a complex geometry while preserving crystal epitaxy. This enables to exploit functionalities given by 3D interconnected pores and suppress charge trapping at defects. One technology that finds it useful is electrochemical energy storage in response to ultrafast alternate current (AC) switch. Here, we extend the concept of 3D mesostructured single crystals to electrochemical capacitors (ECs) for AC line filtering. We present bottom-up epitaxial infilling of Fe3O4 into the self-assembled 300 nm diameter colloid templates using electrodeposition. The resulting 3D mesostructured single crystalline Fe3-delta O4 (111) film (delta approximate to -0.06) is highly oriented along both out-of-plane and in-plane crystallographic orientations. The mesostructured epitaxial electrode responds as an EC capacitor to ultrafast voltage scans at a rate of 50 V s(-1) and exhibits excellent AC line filtering properties at 120 Hz including the small resistor-capacitor time constant (0.86 ms), large areal capacitance (601 mu F cm(-2)), and modest phase angle (-60 degrees). We attribute this to combined effects of efficient charge transport in epitaxial matrix with low defect density and rapid ion diffusion through 3D interconnected periodic pores. The present study demonstrates the power of the 3D structured epitaxy as a tool of advancing the broader area of technology where fast delivery of both charge and mass is important.